Automated Detection and Classification of Sleep Apnea Types Using Electrocardiogram (ECG) and Electroencephalogram (EEG) Features - Kocak, Onur; Bayrak, Tuncay; Erdamar, Aykut; Ozparlak, Levent; Telatar, Ziya; Erogul, Osman (IntechOpen, 2012)
None